Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s11095-005-9225-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific Delivery of Corroles to Cells via Noncovalent Conjugates with Viral Proteins

Abstract: Sulfonated corroles are cytotoxic to ErbB2-positive breast cancer cells when delivered by a targeted cell penetrating protein. The relatively low dose required to accomplish this compared to untargeted compounds suggests that corroles may lend themselves to targeted therapy. Importantly, the amphiphilicity of corroles enables a unique approach to bioconjugate formation whereby the carrier and drug form a stable complex by noncovalent assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 30 publications
(37 reference statements)
6
128
0
Order By: Relevance
“…Because NiSOD exists in nature, we were tempted to synthesize the Ni analogue of MnTE-2-PyP 5þ , but to our disappointment and despite favorable electrostatics and electron-deficiency of porphyrin ligand, the log k cat for NiTE-2-PyP 4þ is only 5.43; it is more than two orders of magnitude less active than MnTE-2-PyP 5þ . Its k cat is around the rate constant for O 2 ·À self-dismutation (5Â10 5 M=s, pH 7.0). Contrary to the porphyrin ligand, the ligand field around Ni in NiSOD enzyme allows it to cycle easily between þ 2 and þ 3 oxidation state with O 2 ·À .…”
Section: O Co and Ni Porphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because NiSOD exists in nature, we were tempted to synthesize the Ni analogue of MnTE-2-PyP 5þ , but to our disappointment and despite favorable electrostatics and electron-deficiency of porphyrin ligand, the log k cat for NiTE-2-PyP 4þ is only 5.43; it is more than two orders of magnitude less active than MnTE-2-PyP 5þ . Its k cat is around the rate constant for O 2 ·À self-dismutation (5Â10 5 M=s, pH 7.0). Contrary to the porphyrin ligand, the ligand field around Ni in NiSOD enzyme allows it to cycle easily between þ 2 and þ 3 oxidation state with O 2 ·À .…”
Section: O Co and Ni Porphyrinsmentioning
confidence: 99%
“…The significant tumor growth suppression and tumorimaging properties of the fluorescent, negatively charged gallium sulfonated corrole noncovalently associated with breast cancer-targeted cell-penetration protein (HerOBK10), which accumulates in HER2 þ tumors, was recently reported; the complex retains integrity in human serum and accumulates in tumor (4,5,43). Nude mice bearing HER2 þ received daily IV injections of 0.008 mg=kg of HerGa complex for 7 days, starting at the time tumors reach 250-300 mm 3 volume; tumor size was measured until 25 days of growth.…”
Section: Corrolesmentioning
confidence: 99%
“…1 For decades, in order to reduce mortality, efforts have focused on new approaches for breast tumor treatment (especially chemotherapy) and its early detection. 2 We recently introduced optical imaging in vivo for chemotherapy assessment, 3 and reported that a tumor-targeted gallium corrole (HerGa), comprising sulfonated gallium corrole (S2Ga) complexed with the recombinant tumor-targeting cell penetrating protein, HerPBK10, is highly effective for killing HER2+ breast cancer cells in vitro 4 as well as for tumor detection and treatment in an animal model of HER2+ breast cancer. 5 In those studies, we used fluorescence intensity imaging to validate the tumor-targeting capability of HerGa in vivo and ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The macrocyclic ring of this complex can be selectively modified to afford molecules that exhibit a wide range of physical and chemical properties (1). Previous work focused on a sulfonic acid derivative of Ga(tpfc), 2 [Ga(2,17-S 2 tpfc)]; notably, 2 possessed potent antitumor activity both in vitro (using human cancer cells) and in vivo (using murine model animals), making it a powerful reagent for both imaging and therapeutic targeting of cancer cells (39,40). Additional studies on the mechanism of cytotoxicity demonstrated that numerous cancer cell lines rapidly take up 2 in vitro and induce cell cycle arrest at late M phase (41,42).…”
mentioning
confidence: 99%